A New Multifunctional DVR for Compensation of Voltage Sag - Srinivasa Rao, N; A. Selwin Mich Priyadharson, Dr (International Journal of Engineering and Technology, 2018)
Now days, power quality is an important application. Sophisticated electronic equipments, variable speed drive having high efficiency,and power electronic controller, are used to improve power quality. Voltage sags are the most common power quality disturbance in thedistribution system. It occurs due to the fault in the electrical network or by the starting of a large induction motor and this can be solvedby using the custom power devices such as Dynamic Voltage Restorer (DVR). It is smaller in size, and provides fast dynamic response tothe disturbance and also has lower cost. A multifunctional DVR is used here to improve the power quality with the help of Posicast andP+Resonant controllers to improve the transient response and eliminate the steady-state error. Simulation result shows the capability ofthe DVR to control the emergency conditions of the distribution systems. The current limitation will restore the point of commoncoupling (PCC) (the bus to which all feeders under study are connected) voltage and Protect the DVR itself. The innovation here is thatthe DVR acts as virtual impedance with the main aim of protecting the PCC voltage during downstream fault without any problem in realpower injection into the DVR.
Keywords: Point of common coupling (PCC); dynamic voltage restorer (DVR); emergency control; voltage sag; voltage swells.